The Comparative Efficacy of Imipenem and Meropenem On Different Bacterial Strains Obtained from Clinical Samples: Imipenem and Meropenem On Different Bacterial Strains - Ahmed Hunjra, Nouman; Ashraf, Aqeela; Niamat, Humaira (Pakistan Journal of Health Sciences, 2022)
The most serious threat to patient's and the public's health is the resistance of clinically relevant microorganisms to antimicrobials. Objective: This study's primary objective was to compare the susceptibility profiles of imipenem and meropenem on various bacterial strains. Methods: 101 distinct patients' positive samples of blood and pus were collected and sent to a pathology lab in Lahore (Mughal Diagnostic and Research laboratory Lahore). On Macconkey, CLED, and Blood Agar media, five bacterial strains; E. coli, P. aeruginosa, Enterococcus species, Klebsiella species and S. typhi were isolated and resurrected. Following microscopical (gram staining) and biochemical tests to identify these bacterial strains, the antibiotic sensitivity of these bacterial strains was assessed. Results: The findings of this investigation clearly demonstrated that imipenem is more sensitive than meropenem. Imipenem demonstrated improved sensitivity to all of the bacterial strains included in the study, especially E. coli, P. aeruginosa, various Enterococcus, Klebsiella, and S. typhi, imipenem showed a sensitivity of 84.15%, while meropenem showed a sensitivity of 40.59%. Conclusions: The current investigation came to the conclusion that antibiotics (imipenem and meropenem) are becoming more resistant to bacteria as a result of their growing and frequent use. Physicians started to worry about the developing antibiotic resistance due to the indiscriminate use of these treatments after more than a decade of increased antibiotic consumption in the era